2012
DOI: 10.1111/j.1744-7402.2012.02834.x
|View full text |Cite
|
Sign up to set email alerts
|

New Non Phyto‐ and Eco‐Toxic Alumina‐Stabilized Silver and Praseodymium Nanoparticles

Abstract: In the present study, we examined how the active aluminum nano‐oxide in the gamma form used as a neutral carrier for the nanoparticles of various metals (as Ag, Pr) affected their toxic behavior. Our experiments have shown that exposure to metal nanoparticles can be reduced by binding the nanoparticles to alumina nanoparticles and the aluminum nano‐oxide is suitable to function as the nano‐stabilizer for the Ag and Pr nanoparticles. We have managed to manufacture new alumina‐stabilized silver and praseodymium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Synthetic nanomaterials are released into the environment with industrial and household wastes, and their release can be expected to increase constantly with their increasing use in industry and increasing share in various consumer products (Jastrzębska et al 2013a). The functioning of natural ecosystems such as water, soil or air and changes in their bio-composition may be seriously disturbed as a result of penetration of GFMs.…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic nanomaterials are released into the environment with industrial and household wastes, and their release can be expected to increase constantly with their increasing use in industry and increasing share in various consumer products (Jastrzębska et al 2013a). The functioning of natural ecosystems such as water, soil or air and changes in their bio-composition may be seriously disturbed as a result of penetration of GFMs.…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…Synthetic nanoparticles are released into the environment with industrial and household wastes, and their release can be expected to increase constantly with increasing use of nanoparticles in industry and their increasing share in various consumer products (Jastrzębska et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Nano-Ag 2 O 3 of 50–80 nm size penetrates fibroblast cells without affecting cell viability or inducing apoptosis. Similarly, when nano-Ag 2 O 3 was used to stabilize nano-Ag or nano-Pr, no phyto- or eco-toxicity was observed (Jastrzębska et al 2012). Our cytotoxic analysis suggests no toxic effect of ZnMgO, and thus potentially its good biocompatibility.…”
Section: Cytotoxicity Analysismentioning
confidence: 99%
“…Many investigation results were reported in the literature concerning bioactivity of the nanomaterials [29][30][31][32]. They have shown that metal oxide nanoparticles were very effective biocides against gram-positive and gram-negative bacteria.…”
Section: Properties Of the Nanopowdersmentioning
confidence: 97%
“…They have shown that metal oxide nanoparticles were very effective biocides against gram-positive and gram-negative bacteria. Many research groups were exploring the different metal oxide nanoparticles for example: aluminum oxide (Al 2 O 3 ) [31,32], iron oxide (Fe 2 O 3 ) [23], titanium oxide (TiO 2 ) [6,17,[33][34][35], zinc oxide (ZnO) [36,37], copper oxide (CuO) [37,38], magnesium oxide (MgO) [39] tin oxide (SnO 2 ) [37], cerium oxide (CeO 2 ) [40] lanthanum oxide (La 2 O 3 ) [37], and zeolites [35] toxicity against bacteria. Most of the tested nanoparticles exhibited relative bactericidal properties against E. coli which is already widely used as a model strain in various toxicity testing.…”
Section: Properties Of the Nanopowdersmentioning
confidence: 99%